Cryptochrome magnetoreception: four tryptophans could be better than three - Wong, SY; Wei, Y; Mouritsen, H; Solov'yov, I; Hore, PJ (Royal Society, 2021)
The biophysical mechanism of the magnetic compass sensor in migratory songbirds is thought to involve photo-induced radical pairs formed in cryptochrome (Cry) flavoproteins located in photoreceptor cells in the eyes. In Cry4a – the most likely of the six known avian cryptochromes to have a magnetic sensing function – four radical pair states are formed sequentially by the stepwise transfer of an electron along a chain of four tryptophan residues to the photo-excited flavin. In purified Cry4a from the migratory European robin, the third of these flavin-tryptophan radical pairs is more magnetically sensitive than the fourth, consistent with the smaller separation of the radicals in the former. Here, we explore the idea that these two radical pair states of Cry4a could exist in rapid dynamic equilibrium such that the key magnetic and kinetic properties are weighted averages. Spin dynamics simulations suggest that the third radical pair is largely responsible for magnetic sensing while the fourth may be better placed to initiate magnetic signalling particularly if the terminal tryptophan radical can be reduced by a nearby tyrosine. Such an arrangement could have allowed independent optimisation of the essential sensing and signalling functions of the protein. It might also rationalise why avian Cry4a has four tryptophans while cryptochromes from plants have only three.